Knowledge and quality of adolescents reproductive health communication between parents and their adolescents children in Ibadan, Nigeria - Musibau A. Titiloye; Ademola J. Ajuwon (AOSIS, 2017)
Communication between parents and adolescents on Adolescent Reproductive Health (ARH) issues are emerging public health concerns in Nigeria; yet they can be tackled through parents' intervention. This study was designed to document the parents' knowledge and quality of communication relating to ARH between parents and their adolescents in Ibadan, Oyo State, Nigeria.A descriptive cross-sectional study was conducted in two Local Government Areas in the state. Interviewer-administered instruments were used to collect data from the parents and adolescents pair. Both instruments included a 28-point knowledge scale and questions on ARH practices. The instrument for adolescents contained an additional 15-point Perceived Quality of ARH Communication (PQARHC). Knowledge scores ≤9, ≤10-18 and ≥20 were categorized as poor, fair and good, respectively for both parents and adolescents. Data were analyzed using descriptive statistics and Chisquare tests at P=0.05. Ages of adolescents were 13.9±2.4 years while parents' ages was 42.6±8.5 years. Parent's and adolescents knowledge scores 22.6±3.4 and 19.4±5.9, respectively with no significant difference. Adolescents whose parents ever discussed ARH issues with them were 20.9% as against 72.1% by the parents. The proportion of parents and adolescents with good knowledge of ARH were 89.4% and 64.7% with no significant difference while the proportion of Adolescents' PQARHC with their parents was adjudged to be of good quality communication was 82.2% with P>0.05. Both the parents and adolescents had good knowledge of adolescent reproductive health but practice and quality of communication was poor. Therefore, training intervention to improve the adolescent- parent communication is recommended for the parents.